2014
DOI: 10.1371/journal.pone.0108777
|View full text |Cite
|
Sign up to set email alerts
|

An Image-Based Genetic Assay Identifies Genes in T1D Susceptibility Loci Controlling Cellular Antiviral Immunity in Mouse

Abstract: The pathogenesis of complex diseases, such as type 1 diabetes (T1D), derives from interactions between host genetics and environmental factors. Previous studies have suggested that viral infection plays a significant role in initiation of T1D in genetically predisposed individuals. T1D susceptibility loci may therefore be enriched in previously uncharacterized genes functioning in antiviral defense pathways. To identify genes involved in antiviral immunity, we performed an image-based high-throughput genetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Additionally, the MAPK gene is involved in the initiation and development of T1D [ 44 ]. HSV1 infection has also been reported to influence T1D progression [ 45 ]. This evidence suggests that the cell cycle and MAPK signaling pathways enriched by KEGG may have an important regulatory role in T1D.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the MAPK gene is involved in the initiation and development of T1D [ 44 ]. HSV1 infection has also been reported to influence T1D progression [ 45 ]. This evidence suggests that the cell cycle and MAPK signaling pathways enriched by KEGG may have an important regulatory role in T1D.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found that TAGAP is involved in HSVmediated induction of the TLR3 pathway 24 , and we first explored the function of TAGAP in macrophages by examining TLR3 or TLR4 ligands-induced signaling pathway activation in bone marrow-derived macrophages (BMDMs) from heterozygous control mice or TAGAP-deficient mice. We did not find any significant difference in terms of signaling activation and gene expression between BMDMs from heterozygous control mice or TAGAP-deficient mice after TLR3 and TLR4 ligands stimulation ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TAGAP has been discovered to have crucial effects through additional pathways and systems, in addition to studies in the tumor immune microenvironment. TAGAP-deficient macrophages had enhanced viral replication of herpes simplex virus type 1, lower expression of pro-inflammatory chemokines and cytokines, and lower production of IFN-β, according to Juan Liao et al., implying that TAGAP plays a significant role in antiviral cytokine production ( 30 ). TAGAP governs the cytoskeletal architecture of actin fibers via RhoA, which is required for cell contractility and the cycle of integrin attachment and separation required for directional migration of thymocytes, according to Jonathan S. Duke-Cohan et al ( 19 ).…”
Section: Discussionmentioning
confidence: 99%